Medidas eletrofisiológicas de crianças com e sem transtornos da comunicação em tarefa de julgamento semântico - Lindau, Tâmara de Andrade (Universidade Federal de São Carlos, 2019)
The interface between language studies and Event-related Potentials (ERPs) has subsidized the investigation for subtle differences in the processing of information that cannot be detected by behavioral measures. This interaction has been considered important in order to investigate and to identify the neural foundations related to the language process and the activated components by the presentation of different stimuli. This dissertation is divided into four chapters: Chapter I presents the theoretical foundations that support the current investigation, including general concepts regarding language and its components and both language and speech sound disorders. Also, the connection between language and electrophysiology is discussed, more specifically about the ERPs and the semantic processing; Chapter II is a review about the compiled literature on semantic processing in children from zero to six years of age, analyzing N400 data. These studies had the common intent of investigating and characterizing the electrophysiological pattern of the semantic processing of younger children in relation to the pattern found in older children and in adults. The analysis indicated great variability of experimental tasks employed, which can affect the level of control and data reliability; Chapter III describes the development of a study whose aim was to investigate the semantic processing, through electrophysiological measures (ERPs), of natural speech sentences in children from four to six years old with and without speech sound disorders (SSD). The results showed that the proposed task allowed to highlight differences in the processing of sentences with congruent and incongruent endings in the two groups studied for the four proposed components: N100, P200, N400 (in two analysis windows) and P600. The waveform (P600) observed for the SSD group, together with the data of the initial components (N100 and P200), may suggest that this group presents deficits in the lexical semantic representations and that changes in the initial processing can also influence later stages of it. The findings pointed out differences in the development of the neural network organization that provides the perception of speech in children diagnosed with SSD. This may suggest that these children set forth neurodevelopmental changes leading to alterations in the initial (perceptual/attentional) processing that influence lexical-semantic representations and later stages of language processing; Chapter IV, eventually, describes the development of another study whose objective was to analyze, individually, the amplitude and latency of the N400 component in SSD children, aiming to verify if the severity of the clinical picture was related to the activation pattern. The results showed that the congruent and incongruent information processing differed in peak latency, but no pattern could be found. It is also observed a variability in the amplitude and latency of the N400 when compared to the different degrees of impairment, making it impossible to speculate on a possible relationship between SSD severity and N400 characteristics in these children, when analyzed individually. This is the first study, among those found in the literature, with the population of children with SSD. Collectively, the findings constitute an important initial contribution and its results may help in the understanding and definition of neural patterns related to speech processing in SSD children. New explorations to consolidate the relations described can increase the knowledge of the neural substrate involved in the development of language skills, aiming to understand the implications of such aspects in the typical and deviant processes of human communication.
Electrophysiological measures in children with and without communication disorders in a semantic judgment task
Keywords: Linguagem; Fala; Transtorno dos sons da fala; Julgamento semântico; Eletrofisiologia; Language; Speech; Speech sound disorders; Semantic judgment; Electrophysiology; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA FISIOLOGICA::NEUROLOGIA, ELETROFISIOLOGIA E COMPORTAMENTO